Neoadjuvant therapy of BRCA1-driven ovarian cancer by combination of cisplatin, mitomycin C and doxorubicin - Tatiana V. Gorodnova; Anna P. Sokolenko; Khristina B. Kotiv; Tatiana N. Sokolova; Alexandr O. Ivantsov; Konstantin D. Guseynov; Ekaterina A. Nekrasova; Olga A. Smirnova; Igor V. Berlev; Evgeny N. Imyanitov (Hereditary Cancer in Clinical Practice, 2021)
Abstract Background Cisplatin, mitomycin C and anthracyclines demonstrate high activity in BRCA1-deficient tumors. This study aimed to evaluate the efficacy of the triplet combination of these drugs in BRCA1-driven high-grade serous ovarian carcinomas (HGSOCs). Methods Ten HGSOC patients with germ-line BRCA1 mutation received neoadjuvant chemotherapy (NACT) consisting of mitomycin C 10 mg/m2 (day 1), doxorubicin 30 mg/m2 (days 1 and 8) and cisplatin 80 mg/m2 (day 1), given every 4 weeks (MAP regimen). The comparator group included 16 women, who received standard NACT combination of paclitaxel 175 mg/m2 and carboplatin (6 AUC), given every 3 weeks (TCbP scheme). Results None of the patients treated by the MAP scheme demonstrated complete pathologic response in ovaries, while 4 women showed absence of tumor cells in surgically excised omental specimens. When chemotherapy response scores (CRS) were considered, poor responsiveness (CRS 1) was not observed in the MAP group, but was common for the TCbP regimen (6/16 (38 %) for ovaries and 5/16 (31 %) for omentum; p = 0.05 and 0.12, respectively). Median treatment-free interval (TFI) was not reached in women treated by the MAP, but was 9.5 months for the TCbP scheme (p = 0.1). The rate of the recurrence within 1 year after the completion of the treatment was 4/10 (40 %) for the MAP and 10/13 (77 %) for the TCbP (p = 0.1). Conclusions The attempt to intensify NACT by administering combination of 3 drugs did not result in high rate of complete pathologic responses. However, there was a trend towards higher efficacy of the MAP regimen versus conventional TCbP scheme with regard to CRS and clinical outcomes.